EVALUATION OF ANTIOXIDANT, ANTI-INFLAMMATORY, ANTI-ALZHEIMER’S AND ANTICANCER ACTIVITIES OF TAONIA ATOMARIA - HANAN F. ALY; EMAN A. IBRAHIM; DOHA H. ABOU BAKER; KHALED MAHMOUD; FAROUK K. EL-BAZ (International Journal of Pharma and Bio Sciences, 2016)
The present research aims to identify the phenolic and flavonoid composition as well as the biological effects of the Taonia atomaria different extracts as antioxidant, anti-inflammatory, anti-Alzheimer’s and anticancer activities against different cancer cell lines including liver cancer cell line (HepG2), colon cancer cell line (HCT116), breast cancer cell line (MCF-7) and ovarian cancer cell line (A549). Beside, antioxidant scavenging activity of T. atomaria using DPPH and ABTS and total antioxidant capacity were also examined. The present results clearly indicated the presence of high contents of e-vanillic acid (4968.78μg/100g), benzoic acid (6286.57μg/100g) and pyrogallol (1531.04μg/100g). In addition, high contents of epicatechein (447.97μg/100g), caffeic (382.19μg/100g), ferulic (380.34 μg/100g) and saiycilic (653.93μg/100g) were found in phenolic composition of T. atomaria. The flavonoid composition of T. atomaria revealed the presence of high content of hisperdin and hespertin with contents 228.61 and 269.06μg/100g, respectively. Also, high content of narengin, rutin and luteolin were observed as they recorded 108.11, 109.19 and 104.01μg/100g, respectively. In addition to, rosmarinic, quercetin, kampferol, apegenin and 7-hydroxy flavone were identified. Moreover, the marine algae T. atomaria different fractions of ethanolic extract exhibited antioxidant, anti- inflammatory, anti-Alzheimer’s and anticancer activities against various cancer cell lines in a dose dependent manner. Thus, it could be concluded that, T. atomaria different extracts demonstrated promising biological activities that needfurther in vivo studies and clinical extensive researches as, anti-inflammatory, anti- Alzheimer’s as well asanticancer agents.